1991
DOI: 10.1161/01.hyp.17.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine overflow and renin pattern of the individual kidney in patients with unilateral renal artery stenosis.

Abstract: This study was performed to determine divided renal efferent sympathetic nerve activity from kidneys in seven patients with renin-positive, unilateral renal artery stenosis before and 30 minutes after an acute intravenous dose of 125 mg enalaprilaL Renal norepinephrine release was calculated from split renal plasma flow, venoarterial plasma concentration gradients across the kidney, and the fractional extraction of tritiated norepinephrine. All patients had unilateral renin secretion, the affected kidney incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The curve relating RSNA to MAP during infusions of graded doses of Ang II was identical to that during infusions of graded doses of phenylephrine, suggesting that the Ang II-induced reduction in RSNA was simply a reflex response to the increase in arterial pressure. Although it has been reported that the activity of the sympathetic nervous system did not increase during Ang II infusion in humans as assessed by measurement of norepinephrine spillover 19 or renal norepinephrine release, 20 the present results provide direct evidence that Ang II does not increase RSNA. Indeed, the results indicate that the pressor response to Ang II is buffered by a decrease in RSNA.…”
Section: Effects Of Ang II On Resting Rsna and Hrcontrasting
confidence: 73%
“…The curve relating RSNA to MAP during infusions of graded doses of Ang II was identical to that during infusions of graded doses of phenylephrine, suggesting that the Ang II-induced reduction in RSNA was simply a reflex response to the increase in arterial pressure. Although it has been reported that the activity of the sympathetic nervous system did not increase during Ang II infusion in humans as assessed by measurement of norepinephrine spillover 19 or renal norepinephrine release, 20 the present results provide direct evidence that Ang II does not increase RSNA. Indeed, the results indicate that the pressor response to Ang II is buffered by a decrease in RSNA.…”
Section: Effects Of Ang II On Resting Rsna and Hrcontrasting
confidence: 73%
“…It has been proposed that angiotensin II interacts with the SNS to facilitate NE release in the kidney. 45 Renal denervation has been shown to delay the onset or decrease the severity of renal hypertension 46,47 and results in a major reduction in renal NE content in SHR and WKY. 47 Dihydrotestosterone also has been shown to have a tissue-specific regulation of renin mRNA in several organs important for blood pressure control, eg, the kidney, adrenal gland, and brain in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the noradrenaline spillover technique is that it has been possible to sample from regional veins and gauge an estimation of sympathetic activity to a variety of organs independently. In a relatively small study in patients with renovascular hypertension, Friberg and colleagues24 found no evidence for increased renal nerve activity in the affected kidney, despite the marked renin production. Another study from this group, however, has shown an increased sympathetic activity to the heart in patients with renovascular hypertensive patients 23.…”
Section: Sympathetic Nervous System and Renovascular Hypertensionmentioning
confidence: 93%